2011
DOI: 10.1097/aln.0b013e3182054d06
|View full text |Cite
|
Sign up to set email alerts
|

Association between Intraoperative Blood Transfusion and Mortality and Morbidity in Patients Undergoing Noncardiac Surgery

Abstract: Background:The impact of intraoperative erythrocyte transfusion on outcomes of anemic patients undergoing noncardiac surgery has not been well characterized. The objective of this study was to examine the association between blood transfusion and mortality and morbidity in patients with severe anemia (hematocrit less than 30%) who are exposed to one or two units of erythrocytes intraoperatively. Methods: This was a retrospective analysis of the association of blood transfusion and 30-day mortality and 30-day m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
224
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(248 citation statements)
references
References 53 publications
8
224
0
5
Order By: Relevance
“…In this series, transfusion requirement was independently associated with 30-day and 90-day major complications. This is consistent with data from 10,100 patients undergoing non-cardiac surgery [29]. A recent report also concluded that that transfusion requirement is associated with reduced survival in non-anaemic patients undergoing radical cystectomy [30].…”
Section: Discussionsupporting
confidence: 81%
“…In this series, transfusion requirement was independently associated with 30-day and 90-day major complications. This is consistent with data from 10,100 patients undergoing non-cardiac surgery [29]. A recent report also concluded that that transfusion requirement is associated with reduced survival in non-anaemic patients undergoing radical cystectomy [30].…”
Section: Discussionsupporting
confidence: 81%
“…10 Additional benefits of the NSQIP database are that data are collected in a standardized manner at each site with strict variable definitions and annual quality checks 10 and the database has been validated for accuracy and reproducibility and achieves a >95% 30-day outcome follow-up rate across consecutive cycles. 10,26 In conclusion, to our knowledge, this is the first prospective, multi-institutional study to assess the relation between age, other preoperative and perioperative risk factors, and short-term outcomes after craniotomy for definitive tumor resection in the elderly (aged !75 years) compared with younger adults. Advanced age (!75 years) was not correlated with poorer short-term outcomes.…”
Section: Limitationsmentioning
confidence: 94%
“…8 Blood transfusions are also correlated with adverse postoperative outcomes and their associated costs, including septic, wound, thromboembolic, and pulmonary complications; longer hospital stays; higher hospital charges; and patient death. [9][10][11] The average risk of transfusion is variable in gynecology and ranges from 0.01% for operative hysteroscopy, 2-5% for operative laparoscopy, 0.3-11% for hysterectomy, 21% for myomectomy, and up to 78% for cytoreductive surgery. [12][13][14][15][16][17][18] However, the overall average risk of a woman requiring a blood transfusion after gynecologic surgery is low making routine testing a high-cost, low-value decision.…”
Section: Introductionmentioning
confidence: 99%